Creep characteristics of austenitic stainless steel foils under oxidative and non-oxidative environment - Fatimah Mohammed Kadhim, 1983-; Mohd. Nasir Tamin, supervisor; Fakulti Kejuruteraan Mekanikal (2015)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2015